Efficiency of an air curtain as an anti‐insect barrier: the honey bee as a model insect. Issue 12 (22nd July 2018) - Kairo, Guillaume; Pioz, Maryline; Tchamitchian, Sylvie; Pelissier, Michel; Brunet, Jean‐Luc; Belzunces, Luc P
Abstract: BACKGROUND: Vector‐borne diseases are of high concern for human, animal and plant health. In humans, such diseases are often transmitted by flying insects. Flying insects stop their flight when their kinetic energy cannot compensate for the wind speed. Here, the efficiency of an air curtain in preventing insects from entering a building was studied using the honey bee as a model. RESULTS: Bees were trained to visit a food source placed in a building. The air curtain was tested with strongly motivated bees, when the visiting activity was very high. Airflow velocity was modulated by setting an air curtain device at different voltages. At the nominal voltage, the anti‐insect efficiency was 99.9 ± 0.2% compared with both the number of bees at a given time in the absence of the air curtain and the number of bees before the activation of the air curtain. The efficiency decreased as the airflow velocity decreased. CONCLUSION: The results show that an air curtain operating at an airflow velocity of 7.5 m s −1 may prevent a strong flyer with high kinetic energy, such as the honey bee, from entering a building. Thus, air curtains offer an alternative approach for combating vector‐borne diseases. © 2018 Society of Chemical Industry Abstract : In the fight against vector‐borne diseases, air curtains may represent a preventive approach. This study shows that an air curtain prevents a strong flyer, the honey bee, from entering buildings.